Ceza Muhakemesi Hukukunda silahların eşitliği ilkesi - Ünal, Ertuğrul (My University, 2020)
Bireysel başvuru yoluyla iç hukukumuza doğrudan etki eden Avrupa İnsan Hakları Mahkemesi, silahların eşitliği ilkesini, adil yargılanma hakkının tabi unsurlarından biri saymaktadır. Sözleşmeye taraf devletlerin, Sözleşmede kabul edilen hakların ihlalini önleme yükümlülüğü bulunduğundan kendi hukuk sistemlerini, Mahkeme tarafından kabul edilen ilkelerle uyumlu hale getirmeleri beklenmektedir.Silahların eşitliği ilkesi, itham sisteminden türemiştir. Bu nedenle tahkik sistemine dayalı ceza muhakemesinde bu ilkenin tatbiki, önemle irdelenmesi gereken bir konudur. Araştırmanın amacı, Türk Ceza Muhakemesi Hukukunun silahların eşitliği ilkesiyle uyumluluğunu, AİHM içtihatları ve Alman Ceza Muhakemesi doktrini ile mukayaseli şekilde ortaya koymaktır.

European Court of Human Rights, which has a direct effect to Turkish legal system through individual application, accepts the equality of arms principle as an inherent element of right to a fair trial. Since the parties of the European Convention of Human Rights have an obligation to meet the standarts of the Convention, it is expected to harmonize legal systems with the principles shown by the Court in the manner most suitable to contracting states’ criminal procedures.The principle “equality of arms” is derivated from the accusatorial criminal procedure. For that reason, it is an important task to combine this concept with the inquisitorial based systems. The purpose of this research is to put forward the complience of Turkish Criminal Procedure with the equality of arms principle in the light of ECHR and German Criminal Procedure Doctrine.
Keywords: Accusatorial Procedure; Adequate Time and Facilities to Prepare a Defence; Adil Yargılanma; Avrupa İnsan Hakları Sözleşmesi; European Convention on Human Rights; Fair Trial; Inquisatorial Procedure; İtham Sistemi; Kamu hukuku; Public law; Right to Examine Witness; Savunmayı Hazırlama İçin Yeterli Zaman ve İmkan; Silahların Eşitliği; Tahkik Sistemi; Tanıkları Sorgulama Hakkı Equality of Arms